Effectiveness of Ultrasound Therapy on Myofascial Pain Syndrome of the Upper Trapezius: Randomized, Single-Blind, Placebo-Controlled Study - Mustafa Aziz YILDIRIM; Kadriye ÖNEŞ; Gökşen GÖKŞENOĞLU (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the effectiveness of conventional ultrasound (US) therapy in the treatment of myofascial pain syndrome. Patients and methods: Fifty-four patients (23 males, 31 females; mean age 29.8±5.2 years; range, 22 to 46 years) with myofascial pain syndrome were included in this prospective, randomized, single-blind, placebo-controlled study. Patients were randomized into two groups by computerized method as US group (n=27) and placebo group (n=27). Ten sessions of US were applied to the US group and 10 sessions of placebo US were applied to the placebo group. Treatment effectiveness was evaluated with Visual Analog Scale (VAS), algometer, palpable muscle spasm degree (PMSD), and Beck Depression Inventory (BDI) before and after treatment. Results: Pain values after treatment in both groups decreased significantly (p<0.05) compared to before treatment. In the US group, the decrease in VAS and palpable muscle degree before and after treatment was significantly higher (p<0.05) than in the placebo group. In the US group, the decrease in PMSD after treatment was significantly higher than the placebo group (p<0.05). The amount of decrease in BDI score before and after treatment in the US group did not differ significantly from the placebo group (p>0.05). Conclusion: Our findings show that conventional US therapy is effective in the treatment of myofascial pain syndrome.